2021
DOI: 10.1111/ajt.16707
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of sensitized lung transplant recipients after peri-operative desensitization

Abstract: Lung transplantation in the setting of preformed donor-specific antibodies (DSA) is frequently avoided due to the risk of hyperacute rejection, early antibody-mediated rejection, and earlier onset of chronic lung allograft dysfunction (CLAD). [1][2][3][4][5][6][7][8] Most lung transplant programs perform virtual crossmatching (VCM) at the time of a donor offer and usually decline an offer for a candidate if DSA are present or accept only if the DSA are felt to be "lower risk" on the basis of their mean fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Our primary survival analysis for the most part corroborates the other single-center studies on crossing DSA at time of lung transplant, but these differences are both notable. 9,10,[20][21][22][23][24] Given these are secondary findings, caution is warranted in their interpretation, and we would first need to consider that they are center-specific observations and potentially confounded by other elements. However, the PGD association in particular remained after adjustment for other PGD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our primary survival analysis for the most part corroborates the other single-center studies on crossing DSA at time of lung transplant, but these differences are both notable. 9,10,[20][21][22][23][24] Given these are secondary findings, caution is warranted in their interpretation, and we would first need to consider that they are center-specific observations and potentially confounded by other elements. However, the PGD association in particular remained after adjustment for other PGD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…One group reported positive outcomes for DSA-positive patients who received TPE, plus IVIG and rituximab if allograft dysfunction occurred (Courtwright, 2019). Another published the long-term outcomes of sensitized lung transplant recipients (N = 146), showing similar rates of allograft and CLAD-free survival compared with unsensitized recipients (N = 194); sensitized recipients received a combination of pre-and post-operative TPE, IVIG, and ATG (Aversa, 2021).…”
Section: Rationale For Therapeutic Apheresismentioning
confidence: 99%
“…8 They report that DSA-positive lung transplant recipients have similar allograft survival and chronic lung allograft dysfunction-free survival to other lung transplant recipients, which is consistent with the prior literature. 4-7 However, they also found that DSAs at the time of transplant were associated with both severe primary graft dysfunction at 48–72 h and AMR, which has been variably reported in prior studies. 4,6,7…”
mentioning
confidence: 85%